MANAJEMEN PENERIMAAN PESERTA DIDIK BARU (PPDB) SISTEM ZONASI (Jurnal Tata Kelola Pendidikan, 2019)
New students admission (PPDB) zoning system policy is considered ineffective in achievinggoal of equitable education access and services in Indonesia. And also considered unableto eliminate people's views about favorite schools, especially in SMA Negeri 2 Tasikmalayawhich has huge enthusiasts, and there were registrants buildup, so that PPDB services heldby schools became less than optimal. This research means to describe management ofimplementation PPDB zoning system in SMA Negeri 2 Tasikmalaya, including planning,organizing, actuating, and controlling. This research used qualitative methods withdescriptive approach. The data sources were head of the branch education office regionalXII, vice principal, and committee of PPDB. The data collection used interviews, anddocumentation study techniques. The results showed that: 1) PPDB zoning system planningincluding understanding of applicable policy, determination requirements, capacity andzoning, budgeting, and socialization. 2) PPDB zoning system organizing is done bydepartmentalization based on dividing division of main tasks and functions of eachcommittee, and adjusted to school needs. 3) PPDB zoning system actuating includingregistration, data input, data verification, selection, announcement of selection results, andre-registration. 4) PPDB zoning system controlling is implemented by the controlling team,head master, branch of education office regional XII, West Java Provincial EducationOffice, mass media and public users of PPDB services. Based on the research results, itwas found that schools were not fully ready for implementing PPDB zoning system becausethere were advantages and disadvantages. So, it needs a massive sosialization to the publicand an evaluation for improving this zoning policy.
Keywords: Management; New Student Admission; Zoning